New insights into the energy metabolism and taxonomy of Deferribacteres revealed by the characterization of a new isolate from a hypersaline microbial mat - Stefan Spring; Manfred Rohde; Boyke Bunk; Cathrin Spröer; Sabine Eva Will; Meina Neumann‐Schaal (Environmental Microbiology, 2022)
Summary Strain L21‐Ace‐BES T , isolated from a lithifying cyanobacterial mat, could be assigned to a novel species and genus within the class Deferribacteres . It is an important model organism for the study of anaerobic acetate degradation under hypersaline conditions. The metabolism of strain L21‐Ace‐BES T was characterized by biochemical studies, comparative genome analyses, and the evaluation of gene expression patterns. The central metabolic pathway is the citric acid cycle, which is mainly controlled by the enzyme succinyl‐CoA:acetate‐CoA transferase. The potential use of a reversed oxidative citric acid cycle to fix CO 2 has been revealed through genome analysis. However, no autotrophic growth was detected in this strain, whereas sulfide and H 2 can be used mixotrophically. Preferred electron acceptors for the anaerobic oxidation of acetate are nitrate, fumarate and dimethyl sulfoxide, while oxygen can be utilized only under microoxic conditions. Aerotolerant growth by fermentation was observed at higher oxygen concentrations. The redox cycling of sulfur/sulfide enables the generation of reducing power for the assimilation of acetate during growth and could prevent the over‐reduction of cells in stationary phase. Extracellular electron transfer appears to be an essential component of the respiratory metabolism in this clade of Deferribacteres and may be involved in the reduction of nitrite to ammonium.

Genome biology of a novel lineage of planctomycetes widespread in anoxic aquatic environments - Stefan Spring; Boyke Bunk; Cathrin Spröer; Manfred Rohde; Hans‐Peter Klenk (Environmental Microbiology, 2018)
Summary Anaerobic strains affiliated with a novel order‐level lineage of the Phycisphaerae class were retrieved from the suboxic zone of a hypersaline cyanobacterial mat and anoxic sediments of solar salterns. Genome sequences of five isolates were obtained and compared with metagenome‐assembled genomes representing related uncultured bacteria from various anoxic aquatic environments. Gene content surveys suggest a strictly fermentative saccharolytic metabolism for members of this lineage, which could be confirmed by the phenotypic characterization of isolates. Genetic analyses indicate that the retrieved isolates do not have a canonical origin of DNA replication, but initiate chromosome replication at alternative sites possibly leading to an accelerated evolution. Further potential factors driving evolution and speciation within this clade include genome reduction by metabolic specialization and rearrangements of the genome by mobile genetic elements, which have a high prevalence in strains from hypersaline sediments and mats. Based on genetic and phenotypic data a distinct group of strictly anaerobic heterotrophic planctomycetes within the Phycisphaerae class could be assigned to a novel order that is represented by the proposed genus Sedimentisphaera gen. nov. comprising two novel species, S. salicampi gen. nov., sp. nov. and S. cyanobacteriorum gen. nov., sp. nov.

Characterization of the first cultured representative of a Bacteroidetes clade specialized on the scavenging of cyanobacteria - Wajdi Ben Hania; Manon Joseph; Boyke Bunk; Cathrin Spröer; Hans‐Peter Klenk; Marie‐Laure Fardeau; Stefan Spring (Environmental Microbiology, 2017)
Summary The anaerobic, mesophilic and moderately halophilic strain L21‐Spi‐D4 T was recently isolated from the suboxic zone of a hypersaline cyanobacterial mat using protein‐rich extracts of Arthrospira (formerly Spirulina ) platensis as substrate. Phylogenetic analyses based on 16S rRNA genes indicated an affiliation of the novel strain with the Bacteroidetes clade MgMjR‐022, which is widely distributed and abundant in hypersaline microbial mats and heretofore comprised only sequences of uncultured bacteria. Analyses of the complete genome sequence of strain L21‐Spi‐D4 T revealed a possible specialization on the degradation of cyanobacterial biomass. Besides genes for enzymes degrading specific cyanobacterial proteins a conspicuous transport complex for the polypeptide cyanophycin could be identified that is homologous to typical polysaccharide utilization loci of Bacteroidetes . A distinct and reproducible co‐occurrence pattern of environmental 16S rRNA gene sequences of the MgMjR‐022 clade and cyanobacteria in the suboxic zone of hypersaline mats points to a specific dependence of members of this clade on decaying cyanobacteria. Based on a comparative analysis of phenotypic, genomic and ecological characteristics we propose to establish the novel taxa Salinivirga cyanobacteriivorans gen. nov., sp. nov., represented by the type strain L21‐Spi‐D4 T , and Salinivirgaceae fam. nov., comprising sequences of the MgMjR‐022 clade.

Pseudomonas benzenivorans sp. nov. and Pseudomonas saponiphila sp. nov., Represented by Xenobiotics Degrading Type Strains - Elke Lang; Melanie Burghartz; Stefan Spring; Jolanthe Swiderski; Cathrin Spröer (Current Microbiology, 2010)

Desulfonauticus autotrophicus sp. nov., a novel thermophilic sulfate-reducing bacterium isolated from oil-production water and emended description of the genus Desulfonauticus - Shanmugam Mayilraj; Anna H. Kaksonen; Ralf Cord-Ruwisch; Peter Schumann; Cathrin Spröer; Brian J. Tindall; Stefan Spring (Extremophiles, 2009)

Cultivated anaerobic acidophilic/acidotolerant thermophiles from terrestrial and deep-sea hydrothermal habitats - Maria I. Prokofeva; Ilya V. Kublanov; Olivier Nercessian; Tatjana P. Tourova; Tatjana V. Kolganova; Alexander V. Lebedinsky; Elizaveta A. Bonch-Osmolovskaya; Stefan Spring; Christian Jeanthon (Extremophiles, 2005)

Biogeochemical transformations of arsenic in circumneutral freshwater sediments - David R. Nicholas; Srividhya Ramamoorthy; Vince Palace; Stefan Spring; Johnnie N. Moore; R. Frank Rosenzweig (Biodegradation, 2003)

Ferribacterium limneticum , gen. nov., sp. nov., an Fe(III)-reducing microorganism isolated from mining-impacted freshwater lake sediments - David E. Cummings; Frank Caccavo Jr.; Stefan Spring; R. F. Rosenzweig (Archives of Microbiology, 1999)